El aprendizaje de los niños desde el estudio de las neuronas espejo en el subnivel elemental, Unidad Educativa “Dr. Manuel Agustín Cabrera Lozano”, Loja 2023 - 2024. - Granda Retete, Zayda Karina (2024)
The Curricular Integration Work, entitled "Learning of Children through the Study of Mirror Neurons in the Elementary Sublevel, at the 'Dr. Manuel Agustín Cabrera Lozano' Educational Unit, Loja 2023 – 2024," seeks to ascertain the mechanisms by which children acquire knowledge through the examination of mirror neurons in the elementary sublevel. This is descriptive research with a mixed approach and a non-experimental design. The theoretical framework addresses the variables of children's learning and mirror neurons. Scientific, descriptive, analytical, synthetic, and statistical methods were employed during the investigative process, contributing to elucidate the curricular integration work. Information was collected through a survey and observation sheet. The researched population comprises four teachers from the elementary sublevel of the 'Dr. Manuel Agustín Cabrera Lozano' Educational Unit. Initial results demonstrate the need for improvement in children's learning, leading to the planning of a guideline: "Innovating Teaching: While I observe, I learn," which was successfully socialized. Its effectiveness was confirmed through positive feedback from teachers regarding the activities, concluding that it constitutes a significant contribution from the perspective of neuroeducation for the enhancement of the teaching and learning process in elementary sublevel core subjects.